Engineering of Reductive Aminases for Asymmetric Synthesis of Enantiopure Rasagiline - Zhang, Kai; He, Yuanzhi; Zhu, Jiawei; Zhang, Qi; Tang, Luyao; Cui, Li; Feng, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Reductive aminases (RedAms) for the stereoselective amination of ketones represent an environmentally benign and economically viable alternative to transition metal–catalyzed asymmetric chemical synthesis. Here, we report two RedAms from Aspergillus calidoustus (AcRedAm) and bacteria (BaRedAm) with NADPH-dependent features. The enzymes can synthesize a set of secondary amines using a broad range of ketone and amine substrates with up to 97% conversion. To synthesize the pharmaceutical ingredient (R)-rasagiline, we engineered AcRedAm through rational design to obtain highly stereoselective mutants. The best mutant Q237A from AcRedAm could synthesize (R)-rasagiline with >99% enantiomeric excess with moderate conversion. The features of AcRedAm and BaRedAm highlight their potential for further study and expand the biocatalytic toolbox for industrial applications.